Report on the Administration of the Improved Seed Saturation Programme in Varanasi Distt. - Planning Commission, Government of India (Planning Commission, Government of India, 1966)
The report evaluates the administration and implementation of the Improved Seed Saturation Programme in Varanasi District, aimed at increasing agricultural productivity through the widespread use of improved seed varieties. The study identifies major shortcomings in organizational coordination, seed production capacity, and distribution mechanisms, which have limited the programme’s effectiveness. It recommends strengthening administrative oversight, improving resource allocation, enhancing training for extension workers, and restructuring distribution through cooperative channels. The findings highlight the importance of a cohesive administrative framework for the successful execution of agricultural development programmes at the district level.
Development Administration Unit Committee on Plan Projects Planning Commission April 1966
Development Administration Unit Committee on Plan Projects Planning Commission April 1966
Keywords: Improved Seed Saturation Programme; Agricultural Administration; Seed Production System; District Level Planning; Agricultural Productivity; Extension Services; Cooperative Societies; Resource Management; Programme Implementation; Varanasi District